Examining the effect of PBL in improving the students’ learning outcomes: A case in a private vocational school - Anwar, Khoirul; Kurniawan, Arief; Purnawan, Purnawan; Ananta, Rendra (Universitas Ahmad Dahlan, 2025)
Vocational education plays a strategic role in increasing the competitiveness of the national workforce. With a work-based learning approach, vocational high schools are expected to be able to bridge the needs of industry through an adaptive curriculum, competency certification, and direct partnerships with the business/industry world. This study aims to describe the procedure for implementing problem-based learning (PBL) in the light vehicle engine maintenance subject, to analyze the improvement in learning outcomes after PBL, and to analyze the extent of the improvement in learning outcomes after the implementation of PBL in the light vehicle engine maintenance subject at SMK Muhammadiyah 1 Moyudan, a private vocational high school in Yogyakarta. This study uses a quantitative quasi-experimental approach (non-equivalent control group design). The PBL was tested on a sample of 60 students. Data were collected through tests and analyzed descriptively, independent t-test, and normalized gain. The results of this study showed a significant difference (sig. 0.004 < 0.05) between the PBL and control groups. The average N-Gain value is 0.54 (medium category). In addition, there is a significant increase in the average value of learning outcomes of class XI TKR B students who use the PBL model to 82, where previously the average value of students only reached 58. The results of this study explain that although both groups experienced an increase, the PBL group showed a greater and more consistent increase than the control group. It proves the significant effectiveness of the PBL in improving the students’ learning outcomes.